Hubungan Pengetahuan, Keadaan Sosial Ekonomi Dan Tindakan Dengan Penanganan Sampah Rumah Tangga Di RT 01/RW 05 Kelurahan Klabulu Kota Sorong - Febry Talakua (Communication and Social Dinamics (CSD), 2021)
Garbage is one of the environmental problems that has long been a concern of the world and needs serious handling so as not to cause harmful impacts. The large pile of garbage will hurt health, the environment, and socio-economic. In Klabulu Village, some people use vacant land or roadside as a garbage dump. If household waste is not handled properly, during the rainy season the waste will be carried away by water and enter the ditch resulting in flooding. The purpose of the study was to determine the relationship between knowledge, socio-economic conditions, and actions for handling household waste in RT 01/RW 05, Klabulu Village, Sorong City. This type of research was quantitative with a cross-sectional study design. The research was conducted in RT 01/RW 05, Klabulu Village, Sorong City in July-August 2020. The population of the study was 50 families. The sample was the head of the family as many as 50 people taken by total sampling. The research instrument used was a questionnaire. Data were analyzed using the Chi-square test with a confidence level of 0.05. The results showed that knowledge p-value 0.029